PENGARUH PERTUMBUHAN PENJUALAN, NON DEBT TAX SHIELD, DEBT SERVICE CAPACITY, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2011-2013 (Students' Journal of Accounting and Banking, 2014)
This research aims to examine and analyze the influence of sales growth, non-debt tax shield, debt service capacity, capital structure and profitability in manufacturing companies listed on the Indonesia stock exchange (IDX) during 2011-2013. The population in this research is the population in this research is a company manufacturing in BEI (Indonesia stock exchange) from 2011-2013. The technique of sampling conducted in purposive sampling, sampling. Based on purposive sampling obtained samples as much as 62 companies. Data analysis technique used was multiple linear regression analysis. Based on the test results it can be concluded that non-debt tax shield variables affect positive toward the capital structure. While the variable sales growth and debt service capacity has no effect on the company's capital structure and profitability of the negative effect of capital structure of the company "was accepted, meaning that the higher the profitability of the company's capital structure, then it will decrease. Keywords: salesgrowth, non-debt tax shield, debt servicecapacity, profitabilityandcapitalstructure